QRS duration: a simple marker for predicting cardiac mortality in ICD patients with heart failure. Issue 10 (15th September 2003) - Bode-Schnurbus, L; Böcker, D; Block, M; Gradaus, R; Heinecke, A; Breithardt, G; Borggrefe, M
Abstract : Background: Patients resuscitated from ventricular tachyarrhythmias benefit from implantable cardioverter-defibrillators (ICDs) as opposed to medical treatment. Patients with increased QRS duration receiving an ICD in the presence of heart failure are at greatest risk of cardiac death and benefit most from ICD therapy. Objective: To determine whether an increased QRS duration predicts cardiac mortality in ICD recipients. Design: Consecutive patients with heart failure in New York Heart Association functional class III were grouped according to QRS duration (< 150 ms, n = 139, group 1; v ⩾ 150 ms, n = 26, group 2) and followed up for (mean (SD)) 23 (20) months. Patients: 165 patients were studied (80% men, 20% women); 73% had coronary artery disease and 18% had dilated cardiomyopathy. Their mean age was 62 (10) years and mean ejection fraction (EF) was 33 (14)%. They presented either with ventricular tachycardia (VT) or ventricular fibrillation (VF). Main outcome measures: Overall and cardiac mortality; recurrence rates of VT, fast VT, or VF. Results: Mean left ventricular EF did not differ between group 1 (33 (13)%) and group 2 (31 (15)%). Forty patients died (34 cardiac deaths). There was no difference in survival between patients with EF > 35% and ⩽ 35%. Cardiac mortality was significantly higher in group 2 than in group 1 (31.3% at 12 months and 46.6% at 24 months, v 9.5% at 12 months and 18.2% at 24 months, respectively; p = 0.04). The recurrence rate of VT was similar in both groups. Conclusions: Within subgroups at highest risk of cardiac death, QRS duration—a simple non-invasive index—predicts outcome in ICD recipients in the presence of heart failure.